Energy savings of an optimized daylight-pipe system with single and dual reflectors in tropical climates of India - Azad, Abdus Salam (2023)
Buildings in India consume over one-third of the country’s total electricity consumption and out of which about 28% and 25% are accounted for lighting energy in the residential and commercial buildings, respectively. Passive daylighting system using tubular daylight-pipe is a promising technique to save lighting energy by illuminating deep building interiors that have no daylight access through exterior windows. In this study, an innovative daylight-pipe has been designed and developed for enhanced daylighting performance by optimizing configurations of single and dual reflectors at its receiver. A detailed daylight assessment has been carried out using controlled experimentation while varying the reflectors position and orientation inside the hemispherical receiver of the daylight-pipe. It has been found that the single reflector oriented toward south has the best performance with a light transmission efficiency of 35.6%. Furthermore, monthly electrical energy savings due to the advanced daylight-pipe along with various supplementary electrical lighting options such as incandescent bulb, compact fluorescent lamp (CFL), and light emitting diode (LED) were estimated and compared for various climatic locations of India. From these evaluations, a lighting energy saving up to 23% has been observed in the summer month of May for temperate climate of Pune and hot-dry climate of Jodhpur.